(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of this study was to determine the meaning, symbols and processes of the Tehununa tradition in the West Seram Regency, precisely in Luhu Village. The research method used is a qualitative method using descriptive analysis. The data analysis technique used in this research is observation, interviews and documentation. The results of this study indicate that tehununa is one of the many traditions that are still being guarded and preserved until now. The Tehununa tradition has two types, namely the Khusu Tehununa and the general Tehununa. The symbols found in the Tehununa tradition are (1) Trees (Tehununa Makatita), (2) food and fruits, and (3) ketupat. The process for the special Tehununa and the General Tehununa has a slight difference in which the Special Tehununa process starts with the intention to carry it out and ends with the process of taking or grabs, while in the General Tehununa it starts from the process of searching for the appropriate tree and ends with the retrieval process.